FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN GAS LPG DI KOTA PEKANBARU (STUDI KASUS GAS LPG 3 KG) - Afdella Rudi Annisa; Harahap Azwar; Basri Syafril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This research was conducted on the 3 kg lpg gas industry in Pekanbaru City. The purpose of this study was to determine how the influence of demand factors for 3 kg lpg gas in Pekanbaru City. The theory used in this research is a theory related to the demand factor, namely Theory of Demand. The type and approach of this research is descriptive research with a quantitative approach. The total population of this study was 100 people who used LPG gas in the city of Pekanbaru. The sampling technique in this study was the stratified random sampling technique, namely stratified random sampling techniques to obtain samples. The data used in this study are secondary data and primary data. Data collection was carried out by means of interviews and questionnaires. The data analysis technique used in this research is multiple linear regression with the help of SPSS (Stastistical Product and Solution) 21 program facilities. The results of data analysis show that the R2 value is 0.738, meaning that the price of the goods itself, the price of other goods, capital income, raw materials , and labor affects the demand for 3 kg lpg gas by 73.8%, while 26.2% is influenced by other variables not included in this research. From the results of the statistical test simultaneously Fcount 90.229> Ftable 3.09, it means that the independent variable price of the goods itself, the price of other goods, and income together influence the dependent variable of the 3 kg lpg gas demand factor in Pekanbaru City. From the results of the partial statistical test, the coefficient value of the price of the goods itself is - .372, the coefficient of price for other goods is 0.158 and the coefficient of income is 0.471 indicating that the variable price of the goods itself has a significant negative effect on the total demand for 3 kg lpg gas in Pekanbaru City, and the coefficient the price of other goods and income have a significant positive effect on the demand for 3 kg lpg gas. and income variable has a dominant influence on the amount of 3 kg lpg gas demand in the city of Pekanbaru because it has the most known regression coefficient of 0.471.Keywords: the price of the goods themselves, the price of other goods, income